Cryptococcus neoformans can form titan-like cells in vitro in response to multiple signals - Trevijano-Contador, Nuria; de Oliveira, Haroldo Cesar [UNESP]; García-Rodas, Rocío; Rossi, Suélen Andreia; Llorente, Irene; Zaballos, Ángel; Janbon, Guilhem; Ariño, Joaquín; Zaragoza, Óscar (Public Library of Science (PLoS), 2018)
Cryptococcus neoformans is an encapsulated pathogenic yeast that can change the size of the cells during infection. In particular, this process can occur by enlarging the size of the capsule without modifying the size of the cell body, or by increasing the diameter of the cell body, which is normally accompanied by an increase of the capsule too. This last process leads to the formation of cells of an abnormal enlarged size denominated titan cells. Previous works characterized titan cell formation during pulmonary infection but research on this topic has been hampered due to the difficulty to obtain them in vitro. In this work, we describe in vitro conditions (low nutrient, serum supplemented medium at neutral pH) that promote the transition from regular to titan-like cells. Moreover, addition of azide and static incubation of the cultures in a CO2enriched atmosphere favored cellular enlargement. This transition occurred at low cell densities, suggesting that the process was regulated by quorum sensing molecules and it was independent of the cryptococcal serotype/species. Transition to titan-like cell was impaired by pharmacological inhibition of PKC signaling pathway. Analysis of the gene expression profile during the transition to titan-like cells showed overexpression of enzymes involved in carbohydrate metabolism, as well as proteins from the coatomer complex, and related to iron metabolism. Indeed, we observed that iron limitation also induced the formation of titan cells. Our gene expression analysis also revealed other elements involved in titan cell formation, such as calnexin, whose absence resulted in appearance of abnormal large cells even in regular rich media. In summary, our work provides a new alternative method to investigate titan cell formation devoid the bioethical problems that involve animal experimentation.